Apparent digestibility coefficient of cotton cake and fishmeal in the feeding of fingerlings of red tilapia (Oreochromis sp.) (Revista Sistemas de Producción Agroecológicos, 2023)
The Apparent Digestibility Coefficients (ADC) of dry matter (DM), crude protein (CP), Ether Extract (EE), Non-Nitrogenous Extract (NNS) and gross energy (GE) of the feed ingredient cotton cake were determined in Oreochromis sp. juveniles (10 ± 2.5 g). In the experiment the reference diet was mixed with the test ingredient in a 70:30 ratio. Chromic oxide was used as an inert indicator. The reference diet and the test diet were fed to Oreochromis sp. kept in confinement at a temperature of 27 ± 2 ºC. Fecal samples were collected by siphoning. The ADCs for DM, CP, EE, ENN and EB of cotton cake were 50.59 ± 2.18, 72.71 ± 1.60, 80.74 ± 0.94, 42.98 ± 3.92, 57.57 ± 2.69, for fish meal were 71.54 ± 3.74, 90.80 ± 4. 34, 89.68 ± 0.56, 63.44 ± 4.69, 76.35 ± 2.68, while the values for the reference diet were 44.27 ± 2.86, 68.43 ± 2.91, 85.11 ± 1.32, 41.48 ± 3.07, 50.38 ± 2.89, respectively. According to the statistical analysis, no significant differences were found between the reference diet and the cotton cake; however, significant differences were found between the reference diet and the fish meal.  Although cottonseed cake has low digestibility levels, due to its extraction methods and biochemical structure, it does not allow a complete assimilation of its nutrients in the digestion of fish; however, in a diet supplemented with other raw materials it can supply nutritional requirements and be very useful to reduce feeding costs due to its low production cost, when used as an alternative raw material.
Keywords: Digestibility Coefficients; feeding; fingerlings